Pre-Emptive Decline - Robert Denemark (Journal of World-Systems Research, 2021)
Why do hegemonic powers appear to have so few viable policy levers with which to cope with their fears of decline, and often adopt policies that are least well-suited, if not antithetical to the task? In this work I suggest that status threat generates a set of typical and quite maladaptive responses at both the individual/organizational level, and in the context of popular political culture, that exacerbate decline. This phenomenon, “pre-emptive decline,” is evident in both elite-driven policy and mass political responses and is reviewed here in maladaptive courses of action adopted in 19th century Britain, and in the contemporary United States.